MENINGKATKAN DAYA SAING PEREKONOMIAN NASIONAL: PELAJARAN DARI INDUSTRI TERPILIH - Maxensius Tri Sambodo; Ahmad Helmy Fuady; Latif Adam; Purwanto Purwanto (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This paper aims to analyze the condition of Indonesian comparative advantage, based on internal and external factors analysis. Based on selected industries namely synthetic fiber, pulp and paper, travel goods and photographic and field research from five provinces, there are some lessons need to be done by government. There are three major findings from this study. First, there is no improvement in competitiveness without increasing value added and productivity. Second, high local content will help the industries to gain competitiveness. Third, currently, contribution of total factor productivity and labor productivity are quite low for enhancing competitiveness. The study suggests government needs to develop up stream industries for supporting downstream industries. Further, promoting good and clean governance need to be part of microeconomic reform.